2021
DOI: 10.1002/cnr2.1469
|View full text |Cite
|
Sign up to set email alerts
|

Inception of a pediatric cancer caregiver support group guided by parental needs

Abstract: Background: Survivorship in childhood cancers has steadily improved and increased the need for caregivers to provide a longer duration of care both in the hospital and at home. Involving parents and caregivers to voice their unmet needs could significantly impact and direct the institution of support groups.Aims: To ascertain the need for a pediatric caregiver support group based on a survey that explored the unmet needs of caregivers of children with cancer.Methods: Caregivers of pediatric patients (n = 17) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Thirteen studies reported unmet needs at an item level (See Table 3) [ n = 11 Cancer (Arabiat & Altamimi, 2013; Ellis & Leventhal, 1993; Levine et al, 2019; Lewandowska, 2022; Lewandowska et al, 2021; Ljungman et al, 2003; Mayer et al, 2009; Mitchell et al, 2006; Moody et al, 2011; Rao et al, 2022; Sloper, 1996); n = 2 CHD (Lesch et al, 2014; Schneider et al, 2020)] with three assessing only unmet informational needs (Ellis & Leventhal, 1993; Lesch et al, 2014; Levine et al, 2019). All studies used a cross sectional design with children at various stages of treatment/post‐treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen studies reported unmet needs at an item level (See Table 3) [ n = 11 Cancer (Arabiat & Altamimi, 2013; Ellis & Leventhal, 1993; Levine et al, 2019; Lewandowska, 2022; Lewandowska et al, 2021; Ljungman et al, 2003; Mayer et al, 2009; Mitchell et al, 2006; Moody et al, 2011; Rao et al, 2022; Sloper, 1996); n = 2 CHD (Lesch et al, 2014; Schneider et al, 2020)] with three assessing only unmet informational needs (Ellis & Leventhal, 1993; Lesch et al, 2014; Levine et al, 2019). All studies used a cross sectional design with children at various stages of treatment/post‐treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies assessed parent-reported needs only, two reported the child's perspective only (Lesch et al, 2014;Lewandowska et al, 2021) and five studies assessed both parent and child needs (Ellis & Leventhal, 1993;Levine et al, 2019;Ljungman et al, 2003;Mitchell et al, 2006;Schneider et al, 2020; See Table 3). Six studies (Lewandowska, 2022;Lewandowska et al, 2021;Ljungman et al, 2003;Mitchell et al, 2006;Rao et al, 2022;Schneider et al, 2020) need assessment tools varied across studies, with three using a standardised scale (Arabiat & Altamimi, 2013;Moody et al, 2011;Schneider et al, 2020). The majority of studies reported the proportion of respondents endorsing each need item, whereas one study reported means for each need item.…”
Section: Studies Reporting Unmet Needs By Itemsmentioning
confidence: 99%
“…We acknowledge that patient and parent support group networks would help identify unmet needs, smoothen patient journeys, and significantly inform future cancer care policies. 16 We understand that positive consumer perception is critical to a health system's performance and have advocated involving families in formulating policy right from the beginning. While community engagement is fundamental to healthcare success, earning their trust and loyalty is the collective responsibility of both public and private healthcare stakeholders.…”
Section: Current Perspectivesmentioning
confidence: 99%
“…Yet, these monumental strides and historical accolades that address significant gaps and inequalities, implement novel solutions, and memorialize the precious lives lost, rarely appear in the academic journals. This special issue of “Patient‐led Research and Advocacy Efforts,” contains 12 articles 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 by patient advocacy groups, parent and survivor organizations from Australia, Chile, Ecuador, India, New Zealand, and the United Kingdom. These articles showcase perspectives, methods, and empirical evidence for notable changes when strong partnerships are built across the cancer treatment trajectory beginning with diagnosis.…”
Section: Figurementioning
confidence: 99%
“…As a child undergoes cancer treatment, their families will face a wide variety of needs. In order to create a support group in India, Rao et al11 conducted a survey to identify the unmet needs of parents of children with cancer. Unmet needs were reported in relation to emotional concerns, informational needs, and treatment side effects.…”
mentioning
confidence: 99%